FAKTOR FAKTOR YANG MEMENGARUHI TINGKAT KELANGSUNGAN HIDUP PASIEN SERANGAN JANTUNG DI IGD RSUD PASAR MINGGU - Talitha Syifa Laili (2023)
Heart attacks are still the leading cause of death in the world. This study aims to determine the factors that influence the survival rate in heart attack patients in the emergency department (ED). This research is retrospective with cross sectional as the research design. The purposive sampling method was used to determine a sample of 112 heart attack patients in 2017-2022. Questionnaires are used as a media for collecting secondary data derived from medical records. The results of Fisher Exact analysis and logistic regression showed that cardiogenic shock was the most significant factor (p=0.000) for death as a result of a heart attack. The odds ratio results showed that female sex, NSTEMI infarction type, active smokers, patients without CKD, and treatment without nitroglycerin therapy were protective factors against death.